Analysis of Financial Feasibility of Anchovy Business (Stolephorus sp) Using Fishing Gear Bagan Tancap in Muara Nibung Village, Pandan District, Tapanuli Tengah Regency, North Sumatra Province - Nasution, Tio Afandi; Zulkarnaini, Zulkarnaini; Hendrik, Hendrik (Jurnal Perikanan dan Kelautan, 2023)
This research was conducted in Muara Nibung Village, Pandan District, Tapanuli Tengah Regency, North Sumatra Province with the aim of knowing the amount of investment, profits and the level of feasibility of fishing for a Bagan Tancap fisherman based on financial aspects of using investment analysis, income, profit, revenue cost (R/C), financial rate of return (FRR), and payback period of capital (PPC). The method used in this study is a survey method while the determination of respondents is carried out by a census. The data collection was carried out by observations, interviews and documentation directly with 37 people of Bagan Tancap fishermen. The results of the study show that the Bagan tancap in Muara Nibung has two categories of operating distance from the coast, including the Bagan dekat ±1 km and the Bagan jauh ±3 km, of course different investments, profit and business feasibility. For Bagan dekat ±1 km the total investment is (IDR 124,616,000.00), the profit received is (IDR 121,240,800.00/year), R/C (2.59), FRR (97.29), PPC (1.03). Whereas Bagan jauh ±3 km the total investment is (IDR 139,416,000.00), the profit received is (IDR 179,140,800.00/year), R/C (2.85), FRR (128.49), PPC (0.78). Based on the results of the calculation that the R/C is more than 1, the FRR is greater than the bank interest rate of 11%, and the PPC is getting smaller, meaning that the fishing business is profitable and feasible to continue.